Calculation of Electromagnetic Force and Temperature Distribution of Amorphous Transformers in Different Operating modes by Finite Element Method - Pham Hong Hai; Bao Doan Thanh (My University, 2023)
Calculation of Electromagnetic Force and Temperature Distribution of Amorphous Transformers in Different Operating modes by Finite Element Method
Keywords: Phân bố nhiệt độ; Finite Element Method (FEM); Chế độ vận hành